Behaviour of precast concrete beam column hybrid connections under seismic type loading - Vidjeapriya, R.; Jaya, K.P. (Journal of Structural Engineering, 2025)
The present work focuses on comparing the performance of two types of precast beam-column connections with that of a monolithic beam-column joint under cyclic loading. In this study, experiments have been conducted on 1/3 scale models of two types of precast and a monolithic connection, designed for the same strength. The specimens have been subjected to reverse cyclic loading. In the first precast connection , the beam is connected to the column with corbel using a cleat angle and for the second precast connection, cleat angle with single stiffener is used .The sub-assemblage specimens have been subjected to cyclic displacement controlled lateral loading applied at the end of the beam. A 400 kN capacity actuator is used to apply the axial load on the column. Actuators with 100 kN and 200 kN capacity with a displacement range of 100 mm have been used to apply the cyclic loading on the beam. The hysteresis behaviour, load carrying capacity, energy dissipation and ductility factor have been measured to compare the performance of the precast and monolithic beam-column connections.